Increase in Growth and Alteration of C:N Ratios of Avicennia marina and Rhizophora stylosa Subject to Elevated CO2 Concentrations and Longer Tidal Flooding Duration - Jacotot, Adrien; Marchand, Cyril; Allenbach, Michel (Frontiers in Ecology and Evolution, 2019)
We investigated the effects of elevated CO2 concentrations and longer tidal flooding duration on more than 1,000 two-year old Avicennia marina and Rhizophora stylosa seedlings during one year. Seedlings were grown in greenhouses for ambient CO2 (400 ppm) and in CO2-controlled closed chambers, installed inside the greenhouses, for elevated CO2 (800 ppm). Tidal flooding duration was set-up conformingly to the species distribution in the intertidal zone in New Caledonia in the controlled treatment, and was increased by 1h45 in the experimental treatment. We measured heights and basal diameters of both species every 90 days, and we determined the above and below ground biomass at the end of the experiment. Our results showed that elevated CO2 increased the growth rates of both A. marina and R. stylosa, for which the final biomass was 46% and 32 % higher, respectively, than the ambient CO2 treatment. We suggest that this augmentation was driven by a stimulation of photosynthesis under elevated CO2, as demonstrated in a previous study. In addition, temperature natural variability played a role on seedlings growth, with higher growth rates during the warm season. Considering the tidal flooding duration treatment, we observed a contrasted effect between species. Longer tidal flooding duration increased the growth of A. marina whereas it reduced the one of R. stylosa in comparison to the controlled treatment. This result may be related to the specific ecosystem zonation in semi-arid climate, which limits water inputs in the Avicennia zone. Eventually, elevated CO2 increased the C:N ratios of the seedlings, therefore producing a more refractory organic matter, which will induce lower decomposition rates and thus may favor carbon accumulation in mangrove soils. These results suggest that future climate changes may enhance the productivity of mangrove seedlings by increasing their growth, which may in turn increase the carbon storage potential of mangroves in their biomass. Recruitment and colonization capacities of mangroves may also be enhanced in the future, which may extend their benefic role in climate change mitigation.